2023
DOI: 10.7575/aiac.ijels.v.11n.2p.108
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Perceptions of Middle School Students Regarding the Concept of Artificial Intelligence

Abstract: Artificial intelligence and technologies have started to directly affect and steer humanity with the developments in science and technology in recent years. Artificial intelligence is like a living organism that thinks, decides and remembers for humans. The effects and consequences of this situation on individuals and societies are explicitly predicted and observed. However, how these results will affect our future in the long term remains a big question mark. It seems likely that countries will add artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In addition, the attitudes of teachers have an important effect on the formation of consciousness and awareness towards AI in students (Ng et al, 2021). Tartuk (2023) examined the metaphorical perceptions of middle school students about AI and found that "students approached the concept of artificial intelligence from a highlevel perspective and explained artificial intelligence by perfecting it to a certain extent" (p. 114). In this respect, it can be said that the results obtained in this study are promising for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the attitudes of teachers have an important effect on the formation of consciousness and awareness towards AI in students (Ng et al, 2021). Tartuk (2023) examined the metaphorical perceptions of middle school students about AI and found that "students approached the concept of artificial intelligence from a highlevel perspective and explained artificial intelligence by perfecting it to a certain extent" (p. 114). In this respect, it can be said that the results obtained in this study are promising for the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, artificial intelligence technology is a critical educational technology and digital learning tool in the 21st century (Taşçi & Durmuşçelebi, 2020). Artificial intelligence technology is effective in education today or in the future (Tartuk, 2023). Artificial intelligence can be utilized in educational activities (Kaban, 2023).…”
Section: Introductionmentioning
confidence: 99%